Economic Contribution of Maine’s Food Industry - Gabe, Todd; McConnon, James; Kersbergen, Richard (Maine Policy Review, 2011)
Using existing state and federal data and Maine IMPLAN, a state-of-the-art economic modeling system, the authors present an overview of the economic contributions of Maine’s food industry. This includes food makers (farms, fisheries, food-processing companies) and food sellers (grocery stores, direct sales, restaurants). Each play a unique, but interconnected, role in the Maine economy and add up to significant economic impact.